43 Reference dosimetry for high dose rate pulsed scanned proton beams. (December 2018) - Vidal, M.; Gerard, A.; Floquet, V.; Peucelle, C.; Rossomme, S.; Herault, J.
Abstract : Introduction: The newly installed ProteusONE (IBA PT, LLN, Belgium) relies on a super-conducting synchro-cyclotron which delivers a pulsed scanned proton beams from 100 MeV to 226 MeV with a dose rate between 2.65 μGy/pulse and 230 μGy/pulse respectively. Its beam structure of 1 kHz frequency and high dose rate per pulse makes it particular considering recombination effect in plane parallel ionization chambers. Methods: The aim of this work is firstly to characterize the beam monitor ionization chambers response in a pulsed scanned proton beam with a high dose rate per pulse, and secondly to find a proper protocol for reference dosimetry with a plane parallel ionization chamber in this kind of proton beams. Following the TRS398 protocol[1], temperature and pressure (kT, P), polarity effect (kpol), beam quality factor (kQ, Q0) and recombination effect (ks) correction factors were computed and applied to the considered ionization chamber. In particular, for a scanned pulsed proton beam the recombination effect in the ionization chamber is not negligible. Therefore, the recombination factor has been theoretically evaluated with Boag's formulae[2] and measured in water for a plane parallel ionization chamber through saturation curves. The quality beam kQ, Q0 factor evaluation was based on Monte-Carlo Goma's results[3] for PBS proton beams. The assumptions made for a high dose rate per pulse pulsed scanned proton beam based on TRS 398 for 3 energies were validated against water calorimetry[4] measurements for 3 energies. Results: The recombination factor study shows that plane parallel ionization chamber should be used with −500 V voltage to limit the effect of recombination. In the same set-up conditions, water calorimetry and ionometry give less than 2% difference for the 3 mono-energetic beams. Conclusions: The presented reference dosimetry protocol is validated for clinical high dose rate per pulse pulsed scanned proton beams.